A comparison study between fuzzy PWM and SVM inverter in NSMC control of stator active and reactive power control of a DFIG based wind turbine systems - Habib Benbouhenni (Institute of Advanced Engineering and Science, 2019)
In this work, we present a comparative study between space vector modulation (SVM) and fuzzy pulse width modulation (FPWM) technique in neuro-sliding mode control (NSMC) of stator reactive and stator active power control of the doubly fed induction generator (DFIG) for wind turbine system (WTS). Two controls approach using NSMC-SVM and NSMC-FPWM control scheme are proposed and compared. The validity of the proposed control techniques is verified by simulation tests of a DFIG. The reactive power, rotor current and stator active power is determined and compared in the above strategies. The obtained results showed that the proposed NSMC with FPWM strategy has stator reactive and active power with low powers ripples and low rotor current harmonic distortion than SVM technique.